Inquiry on infinity in Franz Kafka's The Great Wall of China - Chytrá, Irena (Facultad de Arquitectura, Universidad Nacional Autónoma de México, 2011)
The Great Wall of China -conceived by a visionary and ecclectic architect, Franz Kafka, within an enigmatic and intimate homonymous story- involves a theological analysis concerning the world order. The magnified  notion of the infinity concerns not only the Wall itself, but the Chinese Empire (the darkest among the institutions) and the Emperor himself; including the infinite masses of constructors, their infinite suffering and confusion. Absolutely everything was submitted to the construction of the Great Wall which became the only objective of human existence; meanwhile architecture acquired hegmony in a society entirely devoted to its edification. Nevertheless, Kafka reveals a fundamental contradiction of an absurd endeavor supervised by an invisible and gloomy Headquarters and documented for the future generations by a strange and nameless storyteller -hiding Kafka's identity: the absolute vulnerability of the sober, extremely ambitious but discontinuous wall against the invasions of the Northern tribes, representing the main purpose of its construction. Finally, Kafka's distinctive style -prolific in hyperboles allegories and diachronic contexts- emphasizes a series of existencial and phenomenological metaphors on the transitory and decadent character of both the wall and the Empire whose infinity tends to fade away.